Proceedings of the 2013 ACM SIGSAC Conference on Computer &Amp; Communications Security - CCS '13 2013
DOI: 10.1145/2508859.2516709
|View full text |Cite
|
Sign up to set email alerts
|

Seeing double

Abstract: Of late, threats enabled by the ubiquitous use of mobile devices have drawn much interest from the research community. However, prior threats all suffer from a similar, and profound, weaknessnamely the requirement that the adversary is either within visual range of the victim (e.g., to ensure that the pop-out events in reflections in the victim's sunglasses can be discerned) or is close enough to the target to avoid the use of expensive telescopes. In this paper, we broaden the scope of the attacks by relaxing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In another study [21], 85 % of the participants acknowledged that they had already observed sensitive information on computer screens they were not authorised to see. In addition to direct observation, threats to visual privacy have recently been discussed in the context of surveillance cameras [38], corneal reflections [53], drones [48] and life logging cameras [22].…”
Section: Related Workmentioning
confidence: 99%
“…In another study [21], 85 % of the participants acknowledged that they had already observed sensitive information on computer screens they were not authorised to see. In addition to direct observation, threats to visual privacy have recently been discussed in the context of surveillance cameras [38], corneal reflections [53], drones [48] and life logging cameras [22].…”
Section: Related Workmentioning
confidence: 99%
“…By using supervised learning methods, each key is identified by comparing unknown waveforms with known waveforms collected during training. By video recording [2][3][4][5][6], such as researchers reading computer screens through tiny reflections on glasses, teapots, and other objects. Radio signals captured through surrounding wireless infrastructure, such as using dense cellular deployments to detect nearby human activities, passively listening to CRS broadcasts from base stations to identify victim keystrokes, and analyzing the reflected cellular signals, the inputted PIN was restored on ATM.…”
Section: Introductionmentioning
confidence: 99%